Design And Development Of Light Current Voltage (Liv) Measurement System For Solar Cell Based On Microcontroller - Azehar, Mohamad Hafiz Ahmad (Universiti Sains Malaysia, 2017)
The advantage and improvement of green technology have been widespread all over the world. This has attracted the interest of the government to invest in this sector in which significant solar power capacity had been installed. This will provide an alternative energy sources and at the same time reducing the dependency on expensive imported fossil fuels. The demand for solar technology increases in parallel with the demand of photovoltaic light current voltage (LIV) tester. LIV testers are used to test and verify performance of Photovoltaics devices through LIV curve characteristics and photovoltaic cell parameters. The LIV tester was used extensively in research and development, industrial as well as in commercial activities. The existing LIV testers that were available commercially was too expensive to own. This research is an attempt to design and develop low cost light current voltage (LIV) measurement system based on microcontroller. The tester will be designed and operated close to the standard test condition (STC) for measuring photovoltaic device. The STC test conditions are testing temperature of the sample at 25°C, Solar Irradiance at 1000 W/m2 or solar irradiation intensity of 1 Sun and air mass of 1.5 (AM1.5) spectrum. From the measurement of designed I-V tester gained discrepancy or error of less than 4% for both the open circuit voltage and short circuit current. Despite of that, the maximum power discrepancy reaches about 21% because the current and voltage gained were lower than expected result. This happen because factors of resistance in wires connection and components and accuracy of LED irradiance setup.